Efficacy and safety of immune checkpoint inhibitors in advanced pancreatic cancer: A real world study in Chinese cohort - Xiaoling Gong; Yahui Zhu; Qianning Zhang; Xin Qiu; Changchang Lu; Fan Tong; Qiaoli Wang; Weiwei Kong; Haihui Zhou; Baorui Liu; Yujie Zhou; Juan Du (Taylor & Francis Group, 2022)
Previous clinical studies had not shown expected results in advanced pancreatic cancer (APC) with single-agent checkpoint inhibitors. Until the present day, little is known about their performance in real-world settings. So, in this study, we investigate the ICIs' efficacy and safety in Chinese APC patients. Patients with APC who received ICIs between November 2018 to June 2021 were enrolled in this retrospective study. The efficacy end points included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR) and adverse events (AEs). This study included 104 patients and the median OS (mOS) and median PFS (mPFS) were 9.1 and 5.4 months, respectively. In the subgroup analyses, the mOS was longer for patients receiving combined radiotherapy than for those that didn't (13.8 vs 7.0 months, p < .001), whereas the mPFS was also longer, and the ORR and DCR were higher. Specifically, the mOS was longer for patients who had received a combination of chemotherapy than for those combined with targeted therapy (11.6 vs 5.6 months, p = .002), with the mPFS being also longer. ICIs as a first-line treatment could resulted to better survival. The mOS was longer for patients with a high TMB compared to those with low (19.3 vs 7.2 months, p = .004), whereas AEs were considered to be tolerable. The combination therapy of ICIs was proved to be safe and effective for treating APC, especially the combination of chemotherapy and radiotherapy, which would benefit from additional prospective studies.